(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article proposes to take the European Credit Transfer System (ECTS) as a basis for organizing the educational process using the credit-modular system. The credit-modular organization of the learning process ensures the psychological development of relations between the teacher and the student. These relations contribute to the development of general educational skills and abilities, as well as the independence of students in the educational process.